Maternal And Neonatal Management In The Cases Of HIV / AIDS Infected Pregnant Women In Jambi City - Herlambang Herlambang; Amelia Dwi Fitri; Erny Kusdiyah (Jurnal RSMH Palembang, 2020)
A B S T R A C TBackgrounds: HIV/AIDS is a disease that still becoming a global health problem, andalso became a disease that given special attention by Sustainable Development Goals(SDGs) in 2016 points number 3. In Jambi Province recorded that in the year of 2014the number of cumulative cases of HIV and AIDS is 145 cases of HIV and AIDS 59.Vertical transmission can occur from a mother who is infected by HIV/AIDS to theirbabies. To increase epidemiological knowledge of perinatal outcome from pregnantmother with HIV/AIDS infection, because in Indonesia this type of information is notmuch known, In Jambi This kind of information doesn’t exist. Methods:This is adescriptive research. The data are taken from 41 registers by total sampling. The dataanalysis is using proportion descriptive method. Results: According to 41 datarecorded. 35 neonates (85,4 %) delivered with weight around 2500 gram or more, 41neonates (100 %) delivered with APGAR score (neonatal asthfixia) APGAR 7-9, 32neonates (78,1 %) delivered by Sectio Caesarean, 40 neonates (97.6 %) born at 36weeks, and 25 neonates (60,1 %) delivered from mothers infected by HIV/AIDS withCD 4 counts above 350 cell/ml 41 neonates (100%) born without HIV/AIDS infection.Conclusions: Neoanatal outcome from HIV / AIDS infected mothers in Raden Mattaherthe state hospital of Jambi Province were delivered with normal weight, APGAR score7-9 (normal), delivered by Sectio Caesarea, at the age of 36 weeks or above from motherwith CD4 counts over 350 cell/ml without HIV/AIDS infection.